OCCURRENCE AND STATUS OF POWDERY MILDEW DISEASE ON MAJOR TEMPERATE FRUIT CROPS IN NORTH-WESTERN HIMALAYAN STATE OF JAMMU & KASHMIR (INDIA) (Applied Biological Research, 2026)
Powdery mildew disease adversely affects almost all the major temperate fruit crops leading to huge economic losses. An assessment of powdery mildew disease in important temperate fruit crops of the North-Western Himalayan region of India was conducted during 2021 and 2022. Surveys were conducted in three major districts of Kashmir valley - Srinagar, Pulwama, and Ganderbal - during peak periods conducive to disease development. The disease incidence and intensity recorded in these districts across the key crops revealed moderate to severe infection in apple, pear, quince, grape, and plum, while peach, apricot, walnut, and almond exhibited comparatively lower levels. Quince showed the highest average disease incidence (29.68%) and intensity (24.52%), followed by pear (14.40% and 11.05%), plum (16.39% and 10.76%), grape (12.75% and 8.55%), apricot (9.49 and 7.36%) and apple (8.71% and 5.84%, respectively). In contrast, walnut (3.73% and 2.26%), almond (3.52% and 2.38%) and peach (4.38% and 3.83%) recorded the lowest values. These findings highlight the crop-specific susceptibility pattern and underscore the need for targeted diseasemanagementstrategiesto mitigate the disease pressure, safeguard yield, and ensure sound crop health and sustainable fruit production.
Keywords: Apple, almond, apricot, disease status, grapes, peach, pear, plum, powdery mildew, walnut